Cereals sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
In the 2012-2013 season, high and volatile cereal prices remained a major concern for ACP governments, affecting both access to basic staples and the competitiveness of commercial livestock (largely poultry) production. Although a number of measures to enhance national food production are being taken by ACP governments, major challenges exist in terms of intra-regional and inter-regional cooperation. This Executive Brief provides a detailed analysis of the main trends in the cereal sector in 2012-2013, focusing mainly on the developments in the EU (regarding both CAP support measures and the biofuel mandate) and in ACP countries, where different approaches have been put in place for the development of the cereal sector.